2008
DOI: 10.1002/jemt.20623
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural observations on tegumental surface of Raillietina echinobothrida and its alterations caused by root‐peel extract of Millettia pachycarpa

Abstract: Millettia pachycarpa Benth (Leguminosae) has a usage in traditional medicine system practiced among the Lushai tribes of Mizoram, a state in North East India, who customarily consume the aqueous extract of the root peel of the plant to get rid of intestinal worm infections. The crude ethanol, methanol, and acetone fractions of the plant were assayed against Raillietina echinobothrida, the intestinal cestode parasite of domestic fowl, to authenticate the putative anthelmintic efficacy and cestocidal potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…This is due to the fact that the tegumental and/or cuticular structures are the primary parasite-host interfaces, vital for absorption of nutrients and perception of the surrounding micro-environment provided by the host (William et al 2001;Mckinstry et al 2003;Rivera et al 2004;Xiao et al 2004;Roy et al 2008). Histological studies have revealed that anthelmintic agents induce considerable changes in the internal structural features of helminths, resulting in loss of normal cellular conformity in vital tissues (Roy et al 2008;Dasgupta et al 2010). In the present investigation, the plant extract was shown to cause reduction in the staining activity of the tegumental enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the fact that the tegumental and/or cuticular structures are the primary parasite-host interfaces, vital for absorption of nutrients and perception of the surrounding micro-environment provided by the host (William et al 2001;Mckinstry et al 2003;Rivera et al 2004;Xiao et al 2004;Roy et al 2008). Histological studies have revealed that anthelmintic agents induce considerable changes in the internal structural features of helminths, resulting in loss of normal cellular conformity in vital tissues (Roy et al 2008;Dasgupta et al 2010). In the present investigation, the plant extract was shown to cause reduction in the staining activity of the tegumental enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Control parasites were incubated in PBS having 1% DMSO. Three replicates for each set of incubation medium were used and the time taken for attaining a paralytic state as well as death was recorded as described earlier (Roy et al 2008). Immediately after the onset of paralysis, the parasites incubated in 20 mg of plant extract were selected for histochemical and biochemical studies because of the early effect of the dose when compared with other concentrations.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude ethanol extract and its acetone fraction were made following standard protocol as described elsewhere (Roy et al, 2008). In all, 2.0 g crude ethanol extract was obtained from 100 g dried material which gave about 0.4 g of acetone fraction.…”
Section: Preparation Of Extractsmentioning
confidence: 99%
“…Nowadays, plant materials are employed throughout the industrialized and developing countries as home remedies, over the counter drugs, and ingredients for the pharmaceutical industry. A large number of plant products are being used to combat gastro-intestinal parasites of livestock and also humans [14][15][16][17][18][19][20]. Allium sativum, commonly known as garlic, is one of the species belonging to the family Alliaceae.…”
Section: Background Of the Studymentioning
confidence: 99%